Chemicals for life and living - Ochiai, Ei-ichiro 1936-; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Chemicals often have a negative Image among the general public. But there is no material world or indeed human beings without chemicals. The material world is operated by chemicals. The title 'Chemicals for Life and Living' implies that the material world is staged and played by chemicals.
Essentials of life -- Enhancing human health -- For the fun of life -- What are the earth and the universe made of? -- Chemicals that may cause problems : poisons, pollutants, and others -- Appendix: Essentials of chemistry -- Postscript
Electronic reproduction.
Keywords: Chemistry -- Popular works; Chemicals -- Popular works; Electronic books